2015
DOI: 10.1093/humrep/dev026
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of dioxin-like substances in adipose tissue in patients with deep infiltrating endometriosis

Abstract: Not applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 53 publications
2
36
0
Order By: Relevance
“…Thus, these results although suggestive must be interpreted with caution. While several studies have provided evidence of a potential link significant associations between women with endometriosis and PCB levels could not be demonstrated by other investigators [25,28,31]. No significant association between PCBs and endometriosis risk was found in a study of 789 patients (251 cases; 538 controls); with 20 PCB congers measured in serum from surgically confirmed cases [25].…”
Section: Serum and Omental Fatmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, these results although suggestive must be interpreted with caution. While several studies have provided evidence of a potential link significant associations between women with endometriosis and PCB levels could not be demonstrated by other investigators [25,28,31]. No significant association between PCBs and endometriosis risk was found in a study of 789 patients (251 cases; 538 controls); with 20 PCB congers measured in serum from surgically confirmed cases [25].…”
Section: Serum and Omental Fatmentioning
confidence: 89%
“…Trabert et al [25] 251:538 PCBs 18,28,44,49,52,66,74,87,99,101,118,128,138,146,149,151,153,156,157,167,170,172,177,178,180,183,187,189,194,195,196,201,206 Buck-Louis et al [27] 190:283 and 14:113…”
Section: Polychlorinated Biphenyls (Pcbs) Dioxin and Dioxin-like Commentioning
confidence: 99%
“…Indeed, growing evidence suggests that the peritoneal fluid plays a critical role in the implantation and progression of endometriosis (revised by Koninckx et al 1998). Peritoneal fluid contains detectable levels of dioxin or dioxin-like compounds such as 2,3,7,8-tetrachlorodibenzo-pdioxin (TCDD) depending on individual exposure (Cai et al 2011) and it has been recently shown that the adipose tissue from the omentum in women with endometriosis contains a greater amount of dioxin-like compounds when compared with age and body mass index-matched controls (Martinez-Zamora et al 2015). One can speculate that such compounds are involved in endometriosis as they can transcriptionally induce CYP1B1 and CYP1A1 in explant cultures of human endometrial or stromal cells (Bofinger et al 2001), mostly by their interaction with nuclear receptors, as the resulting complexes bind to the regulatory region of the gene and modulate CYP expression (Waxman 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure in the case–control studies was much lower than in Seveso: Six studies reported no difference in blood levels of PCDD/Fs and DL‐PCBs between cases and controls (Pauwels et al., ; Fierens et al., ; De Felip et al., ; Niskar et al., ; Porpora et al., ; Cai et al., ) One reported lower levels in cases than in controls (Tsukino et al., ) Four reported higher levels in endometriosis cases than in controls (Heilier et al., ; Simsa et al., ; Martínez‐Zamora et al., ; Ploteau et al., ). …”
Section: Assessmentmentioning
confidence: 99%